Power industry disruptors and prospects of the electricity demand in the greater Metro-Manila area - Raul V. Fabella; Geoffrey Ducanes (University of the Philippines, School of Economics (UPSE), 2019)
The power industry is being severely disrupted globally and local industry stakeholders have every reason to be worried. The question is how stakeholder capital should henceforth be deployed to reduce the risk of stranded assets. This study is undertaken to assess the impact of power industry disruptors on the near-term prospect of the electricity demand in the most important submarket of the Philippine power market, the greater Metro-Manila area. The emphasis is on the impact of technology disruptors, especially of solar photovoltaic generation and storage, on top of and in conjunction with policy disruptors. Part One tackles firstly the risks to sustained economic and income growth which will, in turn, impact on the demand for electricity - the macro-economic risks, the global risks, and the policy risks; secondly the risks internal to the electricity industry itself - the technology disruptors especially coming from growing adoption of rooftop and mini-grid solar photovoltaic installations and battery storage. The challenge of solar distributed generation counsels a more sober outlook and a more inclusive portfolio diversification by centralized power generation capitalists. Part Two employs an error correction model to forecast the growth of aggregate and disaggregate (by customer types) demand in a distribution utility franchise, in this case, the Meralco franchise, over the next five years. This model can be adopted as benchmark and adapted by industry stakeholders especially other distribution utility franchises for their own forecasts which should inform the rate setting exercise between the distribution utilities and the regulator, the Energy Regulatory Commission.
Keywords: C53; Q47; Q43; 330; Electricity demand; Forecast methods; Distributed Solar Photovoltaic; Rooftop and Mini-grid systems; Policy disruptors